Conceptual and psychometric properties of a foreign language learning motivation. questionnaire.[article]. - Gonzales, Richard DLC.
This paper investigates the conceptual and psychometric properties of an instrument that measures the foreign language motivation of Filipino learners, The results of this study suggest that there are six factors that compose the motivation orientation of Filipino learners. The factors identified in the questionnaire have the psychometric properties of internal consistence and construct validity. Some further validation, modifications and improvements are also suggested.